Deteksi Keberadaan Nematoda Parasit Elaeolenchus parthenonema Pada Serangga Penyerbuk Kelapa Sawit Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) dari Deli Serdang dan Simalungun Sumatera Utara - Ompusunggu, Hana Herawati; Purba, Josua Aldon; Tamba, Yudi Jhosua; Rahayuwati, Sat; Pradana, Mahardika Gama; Prasetyo, Agus Eko (UNIVERSITAS LABUHANBATU, 2025)
In Indonesia, numerous reports indicate a decline in the population of the oil palm pollinating insect (SPKS) Elaeidobius kamerunicus (Coleoptera: Curculionidae). The parasitic nematode Elaeolenchus parthenonema has not yet been investigated as a potential agent contributing to this SPKS population decline. This research aims are to determine the presence of parasitic nematodes in SPKS populations from Simalungun Regency and Deli Serdang Regency, North Sumatra Province, and to understand the life cycle of these parasitic nematodes. The parasitic nematode E. parthenonema was found, with a low infestation severity per individual SPKS: 1.9 nematodes from Simalungun and 4.94 nematodes from Deli Serdang. Juvenile nematodes (J2, J3) and adults were found in the body cavities of male and female of SPKS imagoes. J2 and J3 were commonly observed in the body cavity, while adults were rarely found. The life cycle of E. parthenonema nematodes begins with J3 exiting from SPKS imagoes and moving to the male oil palm inflorescence to infect the last instar larvae and pupae of SPKS. J3 undergoes two successive molts to become an adult nematode. E. parthenonema is parthenogenetic, so no male nematodes were found. Adult nematodes produce eggs, which then hatch into J1, remaining within the parent’s body. J2 and J3 move out into the SPKS body cavity, consume host’s organ and continuing the life cycle. Keywords: insect, pollinator, nematode, parasitic, oil palm